Genetic and Immunological Determinants of Atopic Dermatitis: A Systematic Review - Lisiecka, Maria Zofia (International Journal of Child Health and Nutrition, 2025)
Purpose: The present work aimed to study the role of genetic and immunological factors in the development of atopic dermatitis (AD). Material and Methods: A thorough systematic search of relevant information on AD presented in the PubMed, ResearchGate, Scopus, Web of Science, and Google Scholar databases for 2010-2023 was carried out. The total number of studies included was 50, with a primary focus on genetic association studies, epigenetic studies, and microbiome studies. Results: The etiopathogenetic mechanisms of the pathogenesis remain under active investigation. It has been determined that the primary factors in the occurrence of AD pathology are the interaction between genetic abnormalities and environmental factors, including climatic factors (temperature, humidity), geographic location (urban vs. rural), air pollution (e.g., particulate matter, ozone), dietary influences (e.g., fat intake, allergens), and exposure to microbes (e.g., pets, infections). An imbalance of the normal intestinal microbiota is a significant predisposing factor. The pathogenetic basis of the disease is an inflammatory process with activation of the T-cell immune response and dysfunction of the genes encoding filaggrin, transglutaminase, and keratin. These disorders lead to increased permeability of the skin barrier and unhindered penetration of allergens. AD is a heterogeneous, multifaceted condition characterised by various endotypes, phenotypes, and clinical subtypes. It frequently commences in early childhood, during the maturation of the immune system and skin barrier. Typical symptoms encompass xerosis, erythema, and pruritus, with affected children exhibiting increased sensitivity to benign irritants, indicative of early immunological dysregulation. Conclusion: AD substantially lowers quality of life and presents mental health risks, especially in young patients. The early onset underscores the necessity for swift action to facilitate immunological development and protect child health.